ANALISIS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS (ILMU PENGETAHUAN ALAM DAN SOSIAL) KELAS IV DI GUGUS 3 JANGKAR TAHUN AJARAN 2024/2025 - Puspitaningtyas, Amalia Risqi; Erinda Nur Kharimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the impact of implementing the Think Pair and Share model in science learning (IPAS) for fourth-grade students in Cluster 3 Jangkar. The research subjects consisted of SD Negeri 1 Kumbangsari as the control group and SD Negeri 2 Kumbangsari as the experimental group. The study employed a Quasi-Experimental method with a Post-Test Only design. The results showed that the use of the Think Pair and Share model had a positive effect on students' learning outcomes in the material of changes in the state of matter in science lessons. Based on the normality test, the data were normally distributed with a significance value of 0.200 for the experimental group post-test and 0.094 for the control group post-test. The homogeneity test showed that the data were homogeneous, with a significance value of 0.623 based on the mean. The t-test results indicated a significance value (2-tailed) of 0.000, meaning H0 was rejected, and H1 was accepted. Therefore, it can be concluded that the use of the Think Pair and Share model significantly affects the learning outcomes of fourth-grade science students in Cluster 3 Jangkar.